Distribution and genetic linkage of coliform bacteria from fish and water from Sarawak river - Ili Liyana, Binti Khlir (Universiti Malaysia Sarawak (UNIMAS), 2012)
Sarawak River plays a major role to human especially in the social and economic activities of Sarawak State. Local fishermen are depending very much on the river to catch raw foods, such as fish, for human consumption. The river also provides water for agriculture activities and acts as place for recreational activities. Coliform bacteria, such as E. coli, have been used as indicator for the microbiological quality of the water and also the fish. In this study, the presence of coliform bacteria in the water and fish samples from Sarawak River were determined and the genetic fingerprint of the bacteria isolates have been used to analyze the genetic diversity of the bacteria in the water and the fish. The samples were collected from three different locations along the Sarawak River; Pending, barrage area, and Waterfront. The coliform bacteria isolated were analyzed and confirmed by biochemical test. Twenty-seven isolates of coliform bacteria were identified. The genetic fingerprint has been carried out by RAPD-PCR analysis. Hence, the study shows that the river is contaminated with coliform bacteria, and the bacteria in the water sample have been found in the fish as well. In term of DNA profile, coliform bacteria in the fish are related to the coliform bacteria in the water.